SYSTEM APPROACH TO INFORMATIONAL SUPPORT OF PHARMACEUTICAL DEVELOPMENT OF FINISHED MEDICINAL PRODUCTS - V. F. Kornushko; A. V. Panov; I. V. Bogunova; O. M. Nikolayeva; A. A. Flid (Тонкие химические технологии)
The article considers the application of the system approach for constructing informational support for the life cycle of the production of medicinal products. The principal difficulties of creating a single informational system of the entire life cycle are considered in this article. A brief analysis of the information and computer support of individual links in the life cycle is given. Particular attention is paid to the use of a systematic approach to the creation of information support for the pharmaceutical development of medicines. The principle of QbD - “Quality planned for development” - was taken as a basis. For the implementation the QbD principle on the basis of the system approach, it is proposed to use the Shewhart-Deming iteration cycle to create an information support for a sustainable search for the optimal version (the program) of the conducted studies. The possibility of combining the PDCA cycle and the methodology of the system approach is shown. On its basis, system-theoretic multiple models of nformation support for pharmaceutical development in the graphic-analytical nomination were constructed. The method of applying the criterial approach for the formation of global and local criteria for managing research and the construction of system management models in the Melentiev’s brackets nomination are presented. The information modeling of the stage of pharmaceutical development has been carried out. Functional models have been constructed in the IDEF0 nomination.